Interpret probability density functions and maximum entropy model for zinc removal in PRDC column by analyzing droplet size distribution - Mehdi Asadollahzadeh; Rezvan Torkaman (Scientific Reports)
Abstract The research discussed in this paper focused on experimental data using a perforated rotating disc column to determine the factors that impact the distribution of drop sizes. A standard test system was utilized, consisting of zinc ions and D2EHPA extractant. When the rotor speed is increased, a majority of droplets display a smaller range of diameters, primarily because of decreased coalescence and increased breakup effects. This column examined how the extraction or stripping stages are influenced by the direction of mass transfer and changes in interfacial tension of the droplets. The findings indicated that the movement of zinc ions between the aqueous and organic phases alters the average droplet size, impacting the distribution of droplet sizes. During the extraction phase, smaller Sauter mean drop sizes were noted in comparison to the stripping phase. A statistical tool was being developed to forecast size distribution by analyzing the relationship between operational factors through the maximum entropy principle. Different probability density functions such as Normal, Lognormal, Gamma, Inverse Gaussian, and Weibull were explored for forecasting size distribution in statistical assessments. By utilizing the maximum entropy technique, the projected probability density function was identified as the most precise based on empirical data, suggesting strong alignment when utilizing this approach to anticipate drop size distribution in the perforated rotating disc column.